Pressure Dependence on the Thermal Conductivity of H‐ and J‐type Nanocomposites. Issue 21 (29th May 2022) - Hong, Younggi; Goh, Munju
Abstract: The dependence of thermal conductivity on molding pressure in composites containing H‐ and J‐type aggregation molecules is investigated for the first time. When mixed with hexagonal boron nitride ( h ‐BN), small molecules capable of H‐ and J‐aggregation significantly affect the orientation of h ‐BN under pressure, resulting in a substantial pressure dependence. For demonstration, 4′, 4′′′‐(1, 2‐diphenylethylene‐1, 2‐diyl)bis(1, 1′‐biphenyl)‐4‐carbonitrile (TPE‐2CP) and 4′, 4′′′, 4′′′′′, 4′′′′′′′‐(ethene‐1, 1, 2, 2‐tetrayl)tetrakis[(1, 1′‐biphenyl)‐4‐carbonitrile] (TPE‐4CP) are synthesized, which exhibit H‐ and J‐aggregation, respectively. Furthermore, epoxy (EP) composites containing TPE‐2CP or TPE‐4CP are prepared, which show different aggregation states with changing pressure. As the pressure increases, the thermal conductivity gradually increases in the radial direction and decreases in the axial direction for TPE‐4CP/EP (and vice versa for TPE‐2CP/EP, but to a lesser extent). Consequently, the pressure dependence of composites with h ‐BN as a filler to TPE‐4CP/EP is also examined. The radial thermal conductivity of this h ‐BN/TPE‐4CP/EP composite increases from 0.8888 W mK −1 at 10 MPa to 1.0062 W mK −1 at 50 MPa. The reasons for the appearance of aggregation states and changes in the thermal conductivity with increasing pressure are then discussed. These findings will contribute to advancing heat dissipation materials by adding TPEs‐based fillers that are biased in one direction using conventional pressure processing techniques. Abstract : The H‐ and J‐type composites show a different pressure dependence of the thermal conductivity. As the pressure increases, the H‐type aggregation composite demonstrates a decreased thermal conductivity pathway in the radial direction, whereas the J‐type aggregation composite showcases an enhanced thermal conductivity pathway in the radial direction.